The quality of life in patients with rectal cancer - Jabłońska, Iwona; Drabik, Urszula (Nursing Problems / Problemy Pielęgniarstwa, 2009)
The quality of the life of patients who underwent anterior resection of the rectum is not satisfactory because of the low anterior resection syndrome. Many authors maintain that the quality of the life after surgery is as important as the good oncological and surgical outcome. The assessment of QOL patients with colorectal cancer is still insufficient. Quality of life is ambiguous, dynamic and variable concept as well. It has various definitions that depend on profession of person who describe the quality of life. However, all conceptions should be analyzed by researcher to right assessment the quality of life. The quality of life researches should be source of information’s of life situation has done by himself. They could prove many valuables information’s of improve ways of work with the patient. That act allow to compare the potential benefits of care with the disadvantageous effects.